2012
DOI: 10.1111/j.1530-0277.2012.01936.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Binge and Escalating Ethanol Exposure Causes Necroinflammation and Fibrosis in Rat Liver

Abstract: A rat model of alcoholic liver disease (ALD) with long-term binge and escalating ethanol exposure was developed. Our data support the hypothesis that enhanced eicosanoid production by COX, oxidative stress and nitrosative stress, HIF-1, and the imbalance between pro- and anti-inflammatory cytokines plays an important role in the pathogenesis of ALD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…Previous work has shown that hepatic insulin resistance and lipid peroxidation are important in the development of ALD (de la Monte et al, 2008;Yao et al, 2006). We have recently used an animal model to help further explore the pathogenesis of alcoholic liver injury (Zhou et al, 2013). EtOH (5 to 9 g/kg/d IG) twice a day (9:00 and 16:00) for 16 weeks was used to mimic the effects of EtOH in the development of ALD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that hepatic insulin resistance and lipid peroxidation are important in the development of ALD (de la Monte et al, 2008;Yao et al, 2006). We have recently used an animal model to help further explore the pathogenesis of alcoholic liver injury (Zhou et al, 2013). EtOH (5 to 9 g/kg/d IG) twice a day (9:00 and 16:00) for 16 weeks was used to mimic the effects of EtOH in the development of ALD.…”
Section: Discussionmentioning
confidence: 99%
“…COX-1 is constitutively expressed in multiple tissues, while COX-2 is inducible by a variety of stimuli. Previous studies have reported the upregulation of COX-2 in cirrhotic livers, which indicates that COX-2 may be involved in the process of liver cirrhosis (6,7). However, the involvement of COX-2 in the progression of liver fibrosis is controversial.…”
Section: Introductionmentioning
confidence: 86%
“…Although no direct correlations have been made between alcohol and tumor hypoxia, alcohol increases HIF-1alpha via oxidative stress in a rat model for alcoholic liver disease [49]. Alcohol is metabolized to acetaldehyde, a known carcinogen, by alcohol dehydrogenase (ADH) situated in the liver, gastric mucosa, oesophageal mucosa and oral mucosa [50].…”
Section: General Conditions Influencing Tumor Hypoxiamentioning
confidence: 99%